2020
DOI: 10.1111/jgh.15217
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of disease severity on capsule endoscopy in patients with small bowel villous atrophy

Abstract: Background and Aim: There is a lack of uniformity of reporting on features of celiac disease (CD) on small bowel capsule endoscopy (SBCE). This makes determining extent of disease and comparison of severity of disease challenging. Methods: De-identified SBCEs of 300 patients (78 CD [26%], 18 serology negative villous atrophy [6%], and 204 controls with normal duodenal histology [68%]) were included. Videos were reviewed by two experts. All patients had duodenal histology taken within 2 weeks of SBCE. The degre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…As with the previous ESGE guideline 1 , there is no new evidence supporting the use of SBCE to routinely map the extent of disease. However, two recent studies from Chetcuti Zammit et al 244 245 reported that the extent of villous atrophy could be efficiently verified by SBCE and atrophy extent could correlate with clinical parameters in some specific subgroups of patients (e. g., those with nonresponsive celiac disease, or severe bone involvement). The first study analyzed SBCE in 300 celiac patients and demonstrated an acceptable agreement among readers to define the severity of celiac disease 244 ; the second analyzed a cohort of 80 celiac patients and showed that, in individuals with a relevant percentage of small bowel involved by villous atrophy, bone mineral density decreased significantly 245 ; furthermore, bone mineral density did not correlate with histological severity of atrophy, underlining the potential relevance of atrophy extent.…”
Section: Celiac Diseasementioning
confidence: 99%
“…As with the previous ESGE guideline 1 , there is no new evidence supporting the use of SBCE to routinely map the extent of disease. However, two recent studies from Chetcuti Zammit et al 244 245 reported that the extent of villous atrophy could be efficiently verified by SBCE and atrophy extent could correlate with clinical parameters in some specific subgroups of patients (e. g., those with nonresponsive celiac disease, or severe bone involvement). The first study analyzed SBCE in 300 celiac patients and demonstrated an acceptable agreement among readers to define the severity of celiac disease 244 ; the second analyzed a cohort of 80 celiac patients and showed that, in individuals with a relevant percentage of small bowel involved by villous atrophy, bone mineral density decreased significantly 245 ; furthermore, bone mineral density did not correlate with histological severity of atrophy, underlining the potential relevance of atrophy extent.…”
Section: Celiac Diseasementioning
confidence: 99%
“…Unless standards in demographics and extent of disease are adhered to [49,50], this will contribute to error propagation and the output algorithm from the machine will also be skewed. A bigger challenge exists in certain conditions such as coeliac disease where there is no standard in reporting on findings in the small bowel and lesions can vary in extent and severity [51,52]. Several limitations exist in recent studies on the use of artificial intelligence in SBCE.…”
Section: Challenges Associated With Artificial Intelligencementioning
confidence: 99%
“…These endoscopic findings suggest the presence of SB mucosal atrophy that is usually, but not always, associated with CeD [ 9 ]. However, the features of SB atrophy at SBCE are not described uniformly, and currently atrophy signs are mainly identified and verified by experts [ 10 ].…”
Section: Introductionmentioning
confidence: 99%